PRODUCTIVITY OF BIOMASS AND LIPID OF Navicula sp. CULTIVATED IN OUTDOOR PHOTOBIOREACTORS) - Gaspersz, Nelson
Research on microalgae as a source of raw material for alternative biofuel production has been carried out. One is Navicula sp. cultured in modified medium (urea, NaH2PO4.2H2O, FeCl3, Na2EDTA, and Na2SiO3.5H2O) showing biomass and lipid productivities of 0.36 g wet cells L–1culture d–1 and 124 ?L oil L–1culture d–1, respectively (Brataningtyas, 2011). Meanwhile, other results showed that the increasing silicate concentration to 450 mg/L culture improved biomass productivity of Navicula sp. to 0.93 g wet cells L–1culture d–1 and the lipid productivity remained unknown (Hairunnisa, 2014). The aim of the present study was to produce biomass of Navicula sp. in modified medium reported previously (Hairunnisa, 2014) in a larger scale using outdoor photobioreactor and to compare with other fertilizer medium optimized. The research methodologies included both indoor and outdoor Navicula sp. cultivation, biomass harvesting, and lipid extraction as well as characterization. The results showed that the growth of marine microalgae Navicula sp. in modified medium in indoor photobioreactors was better than that in outdoor photobioreactors. The highest cell density of Navicula sp. growth in modified medium for 7 d in outdoor photobioreactors was 8.15±0.14 million cells/mL or 4.27±0.037 g wet cells L–1 culture, which was equivalent to a biomass productivity of 0.61±0.007 g wet cells L–1culture d–1. While the highest cell density grown in the same medium and period of growth in indoor was 17.1±0.12 million cells/mL or 5.47±0.26 g wet cells L–1 culture, which was equivalent to a biomass productivity of 0.78±0.038 g wet cells L–1culture d–1. To produce biomass, the best composition of growth medium was variation III containing Hyponex fertilizer, technical Na2EDTA, and technical Na2SiO3.5H2O. The highest cell density of Navicula sp. in fertilizer medium cultivated indoor on the 7th d was 19.05±0,21 million cells/mL or 11.77±0.37 g/L, which was equivalent to the biomass productivity of 1.68±0.051 g wet cell L–1culture d–1. Lipid content of Navicula sp. growth in modified medium in either indoor and outdoor photobioreactors was 20.85 and 37.83%, respectively with lipid productivity of 132 and 222 ?L oil L–1culture d–1, repectively. Some triglycerides of Navicula sp. lipid in indoor cultivation were identified as POP (m/z = 939,63), POO (m/z = 965,64) dan OOO (m/z = 991,66). While, triglycerides of Navicula sp. Lipid in outdoor cultivation were identified as PPPn (m/z=911,68), PnLPn (m/z=931,55), POP (m/z = 939.71), POO (m/z = 965.73), and OOLn (m/z = 989.6).